Globalization, financial crisis and contagion: time-dynamic evidence from financial markets of developing countries - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
Financial integration among economies has the benefit of improving allocation efficiency and diversifying risk. However the recent global financial crisis, considered as the worst since the Great Depression has re-ignited the fierce debate about the merits of financial globalization and its implications for growth especially in developing countries. This paper examines whether equity markets in emerging countries were vulnerable to contagion during the recent financial meltdown. Findings show: (1) with the exceptions of India and Dhaka, Asian markets were worst hit; (2) but for Peru, Venezuela and Columbia, Latin American countries were least affected; (3) Africa and Middle East emerging markets were averagely contaminated with the exceptions of Kenya, Namibia, Nigeria, Morocco, Dubai, Jordan, Israel, Oman, Saudi Arabia and Lebanon. Results have two important policy implications. Firstly, we confirm that Latin America was most prepared to brace the financial crisis, implying their fiscal and monetary policies are desirous of examination and imitation. Secondly, we have confirmed that strategic opening of the current and capital accounts based on empirical evidence for a given region/country as practiced by India is a caution against global economic and financial shocks.
Keywords: G10; G15; F30; 330; Globalization; Financial crisis; Contagion; developing countries; Equity Markets